2014
DOI: 10.1007/s12103-014-9273-3
|View full text |Cite
|
Sign up to set email alerts
|

Arrest Prevalence in a National Sample of Adults: The Role of Sex and Race/Ethnicity

Abstract: We analyzed the prevalence of arrest (ages ranged from 24 to 34) across sex and race/ethnicity by drawing on nationally representative data from the National Longitudinal Study of Adolescent Health. Findings revealed 30 % of U.S. adults (aged 24-34) reported being arrested at least once in their lifetime. Prevalence of lifetime arrest for males (43 %) was more than two times that of females (17 %). Arrest risk was not homogenous across racial/ ethnic groups with 19 % of Asian/Pacific Islander respondents repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 8 publications
2
30
0
Order By: Relevance
“…Racial disparities in arrest are an ongoing issue that should be alarming to the public. Individuals who identify as Black are twice as likely to be arrested as individuals who identify as White (Barnes et al, 2014). Moving beyond examining likelihood for arrest, our study examined differences in frequency of arrest, and after controlling for factors implicating three different theories, we estimate this rate to be seven times greater for Black young adults.…”
Section: Discussionmentioning
confidence: 96%
“…Racial disparities in arrest are an ongoing issue that should be alarming to the public. Individuals who identify as Black are twice as likely to be arrested as individuals who identify as White (Barnes et al, 2014). Moving beyond examining likelihood for arrest, our study examined differences in frequency of arrest, and after controlling for factors implicating three different theories, we estimate this rate to be seven times greater for Black young adults.…”
Section: Discussionmentioning
confidence: 96%
“…We have no trouble believing, for example, that some youngsters are better at focusing in on academic tasks than others (i.e., that there are good students and not-so-good students), or that some people are better at meeting the demands of honest employment than others (i.e., that there are good employees and lousy ones). Yet in much the same way, some people are simply more successful at engaging in crime than others (see generally, Barnes et al, 2015; Brame et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the cumulative prevalence of arrest is significantly higher for males than females, regardless of race/ethnicity, as approximately 12% of females are arrested by the age of 23. Other research similarly demonstrated that approximately 30% of adults (ages 24–34) had been arrested, with a significantly higher prevalence of arrest among Native Americans, Blacks, and Hispanics compared to Whites and Asian Americans [10]. A larger percentage of adult males also self-reported a history of arrest (41%) compared to adult females (17%; [10]).…”
mentioning
confidence: 99%
“…Other research similarly demonstrated that approximately 30% of adults (ages 24–34) had been arrested, with a significantly higher prevalence of arrest among Native Americans, Blacks, and Hispanics compared to Whites and Asian Americans [10]. A larger percentage of adult males also self-reported a history of arrest (41%) compared to adult females (17%; [10]). No known studies from nationally representative samples examine the cumulative prevalence of arrest later in the life course (through late 30s or 40s).…”
mentioning
confidence: 99%